Consumers' Self-Care Algorithms for the Common Cold: Implications for Health Education Interventions - Reis, Janet (Journal of American college health, 2001)
Two hundred ninety-seven young adults enumerated a self-care plan with at least seven behaviors for the management of a cold with a fever. They summarized satisfaction with their self-care activities and the role of self-care after a lecture on self-care in managing the common cold. Half of the participants relied solely on self-care, and the other half said they would seek medical attention. Having a fever directed two thirds of the sample in their decision making concerning treatment. Five percent would change their self-care behaviors as a consequence of the instruction. Methodological and theoretical implications for self-care interventions are discussed.